Profile of Neonatal Septicaemia at a District-level Sick Newborn Care Unit (Journal of Health, Population and Nutrition, 2012)
Although sepsis is a major cause of morbidity and mortality among newborns in resource-poor countries, little data are available from rural areas on culture-proven sepsis. The aim of the present study was to   provide information in this regard. The study reports results on the incidence and aetiology of neonatal sepsis cases admitted to a facility in a rural area in eastern India. Blood culture was done for all babies,   with suspected clinical sepsis, who were admitted to the sick newborn care unit at Suri where the study was conducted during March 2009August 2010. A standard form was used for collecting clinical and   demographic data. In total, 216 neonatal blood culture samples were processed, of which 100 (46.3%) grew potential pathogens. Gram-negative infection was predominant (58/100 cases) mainly caused by   enteric Gram-negative bacteria. Klebsiella pneumoniae was the most common Gram-negative isolate. The emergence of fungal infection was observed, with 40% of the infection caused by yeast. Gram-negative organisms exhibited 100% resistance to ampicillin, cefotaxime, and gentamicin. Amikacin and co-trimoxazole showed 95% (n=57) resistance, and ciprofloxacin showed 83.3% (n=50) resistance among the   Gram-negative bacteria. Carbapenem showed emerging resistance (n=4; 6.6%). Results of analysis of risk   factors showed an extremely significant association between gestation and sepsis and gender and sepsis.   Gastrointestinal symptoms were highly specific for fungal infections. One-third of babies (n=29), who   developed culture-positive sepsis, died. Blood culture is an investigation which is frequently unavailable   in rural India. As a result, empirical antibiotic therapy is commonly used. The present study attempted to   provide data for evidence-based antibiotic therapy given to sick newborns in such rural units. The results   suggest that there is a high rate of antibiotic resistance in rural India. Urgent steps need to be taken to   combat this resistance.   DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11274   J HEALTH POPUL NUTR 2012 Mar;30(1):41-48